Anencephaly: a case report on the rare neural tube defect - Gopalan, Usha Devi; Sagar, Florence Nightingle; Ravi, Sowmiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Anencephaly is a severe, lethal, neural tube defect characterized by the partial or total absence of the brain and calvarium, with a 100% mortality rate either in utero or shortly after birth. It occurs when anterior neuropore fails to close between 23-26 days post-conception, affecting approximately 1 per 1,000 births and is associated with genetic and environmental risk factors such as maternal diabetes, obesity, toxin exposure, and folate deficiency. The condition can be diagnosed early in pregnancy, usually between the 11th and 14th weeks of pregnancy, by USG identifying the lack of cranial ossification and failure to measure the biparietal diameter and also detection through maternal serum alpha-fetoprotein levels. Early diagnosis is essential for effective management and counselling, particularly because of the high likelihood of pregnancy termination due to the fatal prognosis.